Effect of risk management, intellectual capital on performance of state corporations in Kenya: Moderating approach - Grace Girangwa Kakiya; Lucy Rono; Jared Mose (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: The main aim of the study was to determine the moderating effect of intellectual capital on the relationship between ERM risk structure practices and organizational performance of state corporations in Kenya. This study was guided by dynamic capabilities theory which attempts to explain the perspective of how intellectual capital and ERM practices affect organizational performance. Design/methodology/approach: The study used explanatory cross sectional survey design. Primary data on ERM risk structure practices, intellectual capital and organizational performance was collected from structured questionnaires. A survey was carried out on 218 state corporations in Kenya. The research hypothesis was tested using hierarchical regression analysis. Finding: The study found that intellectual capital had an enhancing and significant moderation effect on the relationship between ERM structure practice and organizational performance (ß =.314, p< .05). Originality/value: This study contributes to theory by centering intellectual capital on the empirical testing of theory as well as the influence of intellectual assets on the relationship between enterprise risk management practices and organizational performance. In addition, the study supports the theory of Enterprise Risk Management (ERM) that emphasizes on holistic and company-wide approach of managing risks. The study further suggests that future research could build on this study by examining enterprise risk management practices in different sectors and industries using both financial and non-financial measures of performance.
Keywords: G32; L25; L30; O34; 330; Intellectual Capital; ERM Structure Practices; Organizational Performance